THE MAIN RULES OF THE AESTHETICS OF CLASSICISM IN THE WORK OF THE FRENCH POET BUILLOT (Intent Research Scientific Journal, 2023)
This article provides a detailed account of the famous French poet, critic, and theoretician of classicism, Bouillot Depreault Nicolas, and the main principles of classicism aesthetics in his works and writings.